Functional and radiological outcome of total knee replacement in osteoarthritis with varus deformity - R Sahaya Jose; Visnu Kannan (Journal of Orthopaedic Diseases and Traumatology, 2022)
Aims: The aim of the study is to evaluate the functional and radiological outcome of total knee replacement for osteoarthritis knee with varus deformity, using medial parapatellar approach and posterior stabilized (PS) design. Settings and Design: This is a prospective observational study and nonprobability sampling technique. Materials and Methods: In this prospective study, 20 patients with osteoarthritis knee of Grades III and IV were selected according to Kellgren-Lawrence Grading system. In this study, we assess the functional outcome of total knee replacement using Knee Society Score and radiological outcome using radiographic alignment. The patients were regularly followed up for both functional and radiological outcome at 1st, 3rd, 6th, 12th, and 18 months and then yearly. Statistical Analysis Used: The collected data were analyzed by SPSS 20.00 using the Chi-square test. Results: Preoperatively, our overall mean Knee Clinical and Knee Functional Score was 30.9 and 36.45 which improved to 87.7 and 84 postoperatively with the significant P < 0.001. Our study shows that we have 80% of excellent and 15% good results following total knee replacement. Radiologically all patients have a near-normal radiographic alignment which in turn improves the functional outcome of the patients. Conclusion: Total knee replacement using nonconstrained, PS design and medial parapatellar approach gives functionally excellent pain relief, increased range of motion, restoration of normal function, low prevalence of patellofemoral complications, correction of varus and fixed flexion deformities, and restoration of normal mechanical alignment. Postoperatively, patients with near-normal radiographic alignment like femorotibial angle, posterior condylar offset, and posterior tibial slope have good functional outcome and faster rehabilitation. Correct positioning of the components axially and rotationally improve both the functional and radiological outcome. However, longer follow-up is needed to determine the long-term effect of Posterior Substitute Design.